2014
DOI: 10.1145/2576874
|View full text |Cite
|
Sign up to set email alerts
|

A Crafts-Oriented Approach to Computing in High School

Abstract: In this article, we examine the use of electronic textiles (e-textiles) for introducing key computational concepts and practices while broadening perceptions about computing. The starting point of our work was the design and implementation of a curriculum module using the LilyPad Arduino in a pre-AP high school computer science class. To understand students' learning, we analyzed the structure and functionality of their circuits and program code as well as their design approaches to making and debugging their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(53 citation statements)
references
References 23 publications
(10 reference statements)
2
48
0
3
Order By: Relevance
“…Making is not a unitary activity, and the particular learning outcomes from a robotics club (Cejka, Rogers, & Portsmore, 2006) will likely differ from those found in a sewing circle (Kafai et al, 2014), just as learning outcomes from a half hour making experience at a museum (Bevan et al, 2015) will differ from a multi-year engagement in making in an out-of-school setting (Dixon & Martin, 2017). As such, there is no simple answer to the question, what do youth learn from making, in general.…”
Section: Introductionmentioning
confidence: 99%
“…Making is not a unitary activity, and the particular learning outcomes from a robotics club (Cejka, Rogers, & Portsmore, 2006) will likely differ from those found in a sewing circle (Kafai et al, 2014), just as learning outcomes from a half hour making experience at a museum (Bevan et al, 2015) will differ from a multi-year engagement in making in an out-of-school setting (Dixon & Martin, 2017). As such, there is no simple answer to the question, what do youth learn from making, in general.…”
Section: Introductionmentioning
confidence: 99%
“…Makerspaces serve different audiences across the life span and vary quite widely in terms of media/project emphasis areas, the length of time a maker will work on a given project, and the structure of the community (Sheridan et al, 2014). Makers engage with varied media and technologies to create different products such as programmed e-textiles (Kafai et al, 2014), programmed robots (Fitton, Read, & Dempsey, 2015), 3D-printed or laser-cut building models (McKay, Banks, & Wallace, 2016), multimodal compositions and stories (McGrath & Guglielmo, 2015), and more.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, such assessments typically focus on individual outcomes. For example, adopting Brennan and Resnick's (2012) three-dimensional framework, Kafai et al (2014) assessed individual students' understanding of core CT concepts. They found that remixing (i.e., including segments of existing code into their own design projects) played the most prominent role in CT competence development.…”
Section: Ct and Programmingmentioning
confidence: 99%